(untitled) (PIONIR: JURNAL PENDIDIKAN, 2023)
This research discussed the importance of teacher creativity in shaping children’s character through socio-emotional learning at the Elementary School / Madrasah Ibtidaiyah level. This research aimed to emphasize teachers’ role in helping develop children’s social and emotional skills through collaborative learning and moral teaching in schools. The research location was at MI Nurul Ulum Bantul Yogyakarta. This research used a qualitative approach with interview, observation, and documentation techniques. The research results showed that teacher creativity in forming children’s character through socio-emotional learning at MI Nurul Ulum was 1) generating motivation to learn with technology, 2) making the material relevant to everyday life, 3) presenting an interesting impression when learning, 4) making teachers as a role model for children, 5) creating a communicative learning atmosphere, and 6) understanding children’s moods when learning.